PENGELOLAAN KONFLIK PASANGAN ASMARA YANG BERKENALAN DAN BERKOMITMEN MELALUI SOSIAL MEDIA TINDER - Rizky F, Annisa; Naryoso, Agus (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
The presence of Tinder social media is seen as a solution to get partners for some of its users, the use of Tinder in Indonesia itself has sufficiently developed and becomes increasingly in demand by teenagers and adults. Survey shows that 59.3% of Tinder users are male and Tinder itself is most downloaded by those aged 25-34 years, which amounted to 51.9%. Interestingly, Indonesia is ranked 7th as the most downloaders and online dating users in the world. However, along with the many users of Tinder social media in Indonesia, there are also many conflicts that can be obtained through Tinder. Based on the data of Application Poll (Jakpat) in 2017, there were 512 respondents aged 16-45 years who said that there were 12.52% of the online dating application users that have experienced verbal and visual harassment when accessing Tinder. Besides, there are many Tinder users who increasingly suspect and experience uncertainty, due to the low level of trust as well as knowledge of the potential partner. This study aims to determine how the conflict management and uncertainty reduction are conducted by individuals when they choose to meet up and decide to date partners that they met in Tinder. This study uses a qualitative method with phenomenological approach as well as the basic theory of maintenance relationship developed by Steford and Canary and the uncertainty reduction theory developed by Charles Berger. Data collection technique used in this research is in-depth interviews with the research subjects of lovers who met in social media Tinder and often falsify their identity until they decide to continue their relationship as in dating and one female informant who use ocial media Tinder with a false identity. The results show that couples who met and committed love through social media Tinder manage conflict by being silent and distant to his or her partner. It aims to avoid undesirable things as well as emotions that continue to remain inside. In addition, couples who met through Tinder often do stalking in order to reduce uncertainties.